PENGLIHATAN BINOKULAR PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS AIRLANGGA ANGKATAN 2014 DENGAN METODE TITMUS - Aziza Rahma Dewanti, NIM011411133040 (2017)
Background : Binocular Single Vision may be defined as the state of simultaneous vision, which is achieved by the coordinated use of both eyes, so that separate and slightly dissimilar images arising in each eye are appreciated as a single image by the process of fusion. Stereopsis is the highest form of binocular cooperation which adds a new quality to vision. Binocularity appears to be an advantage in certain professions, such as surgeon, dentist, architect, baseball player. The quality of binocular vision, i.e. whether bad or good, can be determined by measuring or assessing the stereo acuity. In this study, researchers conducted a binocular vision examination in medical students of Airlangga University class of 2014 who were included in the inclusion criteria at poli mata RSU Dr.Soetomo Surabaya. Method : In this descriptive study, 109 students of Airlangga University of Medicine Class of 2014 served as subjects. The binocular vision was examined using Titmus test for their stereo acuity. Results : Total of 109 university students between 19-22 years old was included in this study with 30 boys and 79 girls. The average stereo acuity was 51.8 seconds of arc. Furthermore, 103 (95%) students had normal stereo acuity (60 seconds of arc or better).